Antibiotic resistance: a challenge for the meat processing industry – a review - Ștefania Alina Brașoveanu; Diana Mihaela Alexandru; Irina Macovei; Ionuț Gheorghe; Constantin Savu (Medicamentul Veterinar)
Antibiotic resistance (ABR) has direct and indirect repercussions on public health and threatens to decrease the therapeutic effect of antibiotic treatments and lead to more infection-related deaths. There are several mechanisms by which ABR can be transferred from one microorganism to another. The risk of transfer is often related to environmental factors. The food supply chain offers conditions where antibiotic resistance gene transfer can occur by multiple pathways, which generates concerns regarding food safety.